Vegetative shoot growing and yield productivity of different plum cultivar and rootstocks combination - Czinege, Anikó; Nyéki, József; Soltész, Miklós (Acta Agraria Debreceniensis, 2012)
We planted containers plum rootstocks and cultivar combinations for irrigation and rootstocks experiment. We planted Cacanska lepo tica, Katinka, Jojo, Topfive, Toptaste, Topper plum cultivar on Mirobalan, St Julien A, St Julien GF 655/2, Wavit, Wangenheim, and Fereley rootstocks. Before budding we measured the trunk diameter on trees, than I count the trunk cross area, we measured the high of trees, the high of crown, and the wide of crown, and counted the volume of crown from these data. We conclude the vigorous from the trunk cross area and the volume of crown. In the started growing less vigorous combinations look like Topfive/Wavit, Jojo/Mirobalan and Katinka/Mirobalan grafted on the basis trunk cross area and the volume of crown. In the vegetative period we measured the shoot growing on model branch every started of months. So we could determine the growing tendency. The smallest growing was Cacanska lepotika/Mirobalan. In the flowering the grafted flowered in rich, excepted the Topfive cultivar on St Julien A, St Julien GF 655/2, and Fereley rootstocks, these didn’t flowered. The Topfive/Wavit combinations there were a richest flower. In the harvest term we could pick up plum fruits from Topfive/Wavit combinations, and Cacanska lepotica, Jojo, Toptaste cultivar. And in addition the Topper cultivar was the highest yield on their all of rootstocks.